Control of an external force in leg extensions in humans - Jacobs, R.; van Ingen Schenau, G. J. (The Journal of Physiology, 1992)
1. We investigated the hypothesis that mono- and bi-articular muscles perform different functions: the former are chiefly dependent on their mechanical advantage, while the latter are considered to be mainly concerned with controlling the direction of an external force. 2. Seven subjects were asked to exert a constant external force in various directions from three different positions. Feedback was given on the amplitude (300 and 600 N) and direction of the force vector. 3. During each trial the position of the subject was registered. Ground reaction force and muscle activity (EMG) from the main mono- and bi-articular upper leg muscles were recorded. Link segment modelling was used to obtain net moments about the knee and hip joints. For each muscle the mechanical advantage was calculated in each force direction. 4. The task of controlling the ground reaction force was performed with little interindividual variation as reflected by the variability of the different force and EMG variables. 5. A linear relationship between the difference in activity of rectus femoris and hamstrings and the difference in net moment around the knee and hip was found. This relationship showed very high correlation coefficients of 0.96 (300 N) and 0.97 (600 N) and was independent of position. Mean correlations between this activity difference and the angle of the force vector were also high: -0.95 (300 N) and -0.94 (600 N). 6. The mono- as well as the bi-articular muscles increased in activity when a larger mechanical advantage could be obtained from them, except for the biceps femoris (short head). 7. The results support the hypothesis that bi-articular muscles have a unique role in controlling the distribution of net moments about the joints, and as a consequence, in controlling the direction of the external force exerted on the environment.